Effect of temperature on dielectric properties and penetration depth of oil palm shell (OPS) and OPS char synthesized by microwave pyrolysis of OPS - Tripathi, M.; Sahu, J.N.; Ganesan, P.; Dey, T.K. (Elsevier, 2015)
Microwave-assisted pyrolysis is a promising technique for thermochemical treatment of various feedstocks mainly due to its efficient heating by 'conversion of electromagnetic energy into heat'. Microwave heating largely depends upon the dielectric properties of the material to be exposed to microwave radiation. Temperature dependence of dielectric properties along with penetration depth of oil palm shell (OPS) and OPS char have been investigated in the temperature range from 30°C to 600°C at 915 MHz and 2450 MHz frequencies. Measurement is made by HP 85070B open-ended coaxial probe attached to computer controlled HP 8722D Vector Network Analyzer (VNA). At room temperature, dielectric constant of OPS is higher than that of OPS char for both the frequencies. Dielectric constant and dielectric loss of both these materials decrease with the increase in the temperature. At room temperature, penetration depth corresponding to 2450 MHz is found to be lower as compared to that at 915 MHz frequency for both the materials, which makes 2450 MHz frequency to be more appropriate for microwave heating applications. Rise in temperature is seen to produce an increase of the penetration depth for both the materials. High dielectric constant and low penetration depth of OPS as compared to OPS char makes OPS to be more suitable for microwave heating. Experimental results of dielectric constant for both the materials are fitted to Boltzmann and Gauss models. Gauss model fits the experimental data of OPS more accurately while Boltzmann model is more suitable for OPS char.